Diseño y elaboración de recursos didácticos para el aprendizaje de la Matemática en el subnivel elemental de Educación General Básica de la Unidad Educativa Quito. - Mena Mena, Verónica Mercedes (2020)
The Resources and Didactic Materials in the first years of Basic Education in the area of Mathematics are important, its planned and strategic use guarantees student learning, in these circumstances when in the learning process the specific phase is not given to the children the opportunity to manipulate objects, the possibility of forming schemes, knowing the object better, relating and establishing relationships between objects, to move to the graphic and symbolic phase, which implies an absolute flaw in the abstraction concepts and cannot apply them in the resolution of everyday problems. Hence, the objective of this research work is to develop a guide of innovative teaching Resources for the Mathematics learning in the children of the elementary level of the “Quito” Educational Unit. The research has a quantitative and descriptive approach; for information gathering, the structured interview technique and the survey were used, through the application of instruments such as the question guide and the questionnaire. The results evidenced the need to prepare a proposal of active teaching resources for the learning of mathematics in the Basic General Education Elementary Level, which was submitted to a theoretical validation process of experts and users.